OMANIAN ENTREPRENEUR PROFILE AND BEHAVIOR - Lavinia Mirabela JIANU (BORCOS); Oana Mihaela BARA (Management & Marketing)
Due to major contribution of the entrepreneurs to the economic and social development, the knowledge of their main characteristics has a special significance The paper presents the results of a economic research conducted in April and May 2014 and offers an exhaustive approach on the characteristics and behavior of the Romanian entrepreneur, a lot of aspects being analyzed which are not present in other researches.According to this research, the Romanian entrepreneur’s profile is the following: a mature individual, holding an economical background, of male sex, married, with children, with high education.